Fireworks induced particle pollution: A spatio-temporal analysis - Kumar M.; Singh R.K.; Murari V.; Singh A.K.; Singh R.S.; Banerjee T. (My University, 2025)
Diwali-specific firework induced particle pollution was measured in terms of aerosol mass loading, type, optical properties and vertical distribution. Entire nation exhibited an increase in particulate concentrations specifically in Indo-Gangetic Plain (IGP). Aerosol surface mass loading at middle IGP revealed an increase of 56-121% during festival days in comparison to their background concentrations. Space-borne measurements (Aqua and Terra-MODIS) typically identified IGP with moderate to high AOD (0.3-0.8) during pre-festive days which transmutes to very high AOD (0.4-1.8) during Diwali-day with accumulation of aerosol fine mode fractions (0.3-1.0). Most of the aerosol surface monitoring stations exhibited increase in PM2.5 especially on Diwali-day while PM10 exhibited increase on subsequent days. Elemental compositions strongly support K, Ba, Sr, Cd, S and P to be considered as firework tracers. The upper and middle IGP revealed dominance of absorbing aerosols (OMI-AI: 0.80-1.40) while CALIPSO altitude-orbit-cross-section profiles established the presence of polluted dust which eventually modified with association of smoke and polluted continental during extreme fireworks. Diwali-specific these observations have implications on associating fireworks induced particle pollution and human health while inclusion of these observations should improve regional air quality model. © 2016 Elsevier B.V.